We are the world and the world is our home: Learning about the environment and taking care of it in the primary classroom - Rosenberg, Ethel Rosa (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Intercultural and human rights education should be always present in every lesson plan, since it is from there that the concepts of inclusion and diversity can be really experienced. This project intends to raise awareness on environmental issues such as water saving and deforestation, through language learning, comparison and contrast between two cultures, and an emphasis on the rights and responsibilities we all have as cosmopolitan citizens.